Are They Really Ready to Work? Employers' Perspectives on the Basic Knowledge and Applied Skills of New Entrants to the 21st Century U.S. Workforce - Casner-Lotto, Jill; Barrington, Linda (Partnership for 21st Century Skills, 2006)
In collaboration, The Conference Board, Corporate Voices for Working Families, the Partnership for 21st Century Skills, and the Society for Human Resource Management conducted an in-depth study of the corporate perspective on the readiness of new entrants into the U.S. workforce by level of educational attainment. The study includes results from both an in-depth survey conducted during April and May 2006 and interviews with a sampling of a dozen HR and other senior executives. In addition, a Workforce Readiness Report Card is presented to provide an accessible snapshot of the basic knowledge and applied skills that are either "deficient" or "excellent" in those areas that employer respondents rate as "very important." This research defines Workforce Readiness by asking employer respondents: (1) Whether or not the skill levels that new entrants are currently bringing to their jobs are deemed "excellent," "adequate," or "deficient"; (2) What basic knowledge and applied skills they consider "very important," "important," or "not important." Basic knowledge refers to the academic subjects and skills acquired in school. Applied skills refer to those that enable new entrants to use what they learned in school to perform in the workplace; (3) How the importance of these skills may change over the next five years; (4) What emerging content areas are considered "most critical" over the next five years; and (5) What are the nature and costs of remedial training or initiatives, if basic skills are lacking. The data are typically presented throughout the report separately for high school, two-year college/technical school, and four-year college levels. About the Survey is appended. (Contains 13 tables, 3 charts and 32 footnotes.) [This research was conducted in collaboration of The Conference Board, Corporate Voices for Working Families and The Society for Human Resource Management. Additional funding for this paper was provided by Dell Inc., Philip Morris USA Youth Smoking Prevention, SAP and State Farm.]